Dynamics of skill acquisition in figure skating - Part 3 - Lucash, G.; Davids, K.; Otte, F. (The Professional Skater PS Magazine, 2021)
Dritter Teil einer vierteiligen Beitragsserie zur Dynamik des Fähigkeitserwerbs im Eiskunstlauf